2014
DOI: 10.1002/nau.22654
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle training for bowel dysfunction following colorectal cancer surgery: A systematic review

Abstract: Pelvic floor muscle training for patients following surgery for colorectal cancer appears to be associated with improvements in bowel function and HRQoL. Results from non-randomized studies are promising but randomized controlled trials with sufficient power are needed to confirm the effectiveness of PFMT in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 49 publications
0
27
0
4
Order By: Relevance
“…Dietary restrictions, high fibre consumption, and probiotics are advised, although no data support the benefit of those agents. For major LARS patients, additional procedures such as pelvic floor rehabilitation (in the form of biofeedback, electrostimulation, pelvic floor muscle training, and volumetric training) and transanal irrigation are available and of some benefit [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary restrictions, high fibre consumption, and probiotics are advised, although no data support the benefit of those agents. For major LARS patients, additional procedures such as pelvic floor rehabilitation (in the form of biofeedback, electrostimulation, pelvic floor muscle training, and volumetric training) and transanal irrigation are available and of some benefit [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…the majority of studies reported significant improvements in stool frequency, incontinence episodes, severity of fecal incontinence, and health-related quality of life after pelvic floor muscle training and biofeedback. 15 however, a multimodal approach, performed managing with some rehabilitative techniques such as biofeedback, pelvic floor muscle training, electrostimulation, and volumetric/rectal balloon training according to the individual needs of the patient, could significantly improve symptoms 16 more than individual techniques alone. moreover, irradiated patients show short-and long-term training effects comparable to those of nonirradiated patients despite the higher degree of incontinence at baseline.…”
Section: Treatment Algorithmmentioning
confidence: 97%
“…The immunohistochemical study of pelvic floor muscles had shown that female patients with POP or SUI have muscle fiber damage [10]. Changes in the pelvic floor muscles cause changes in their dominating muscles, which provides a morphological basis for nerve damage that can cause damage to the pelvic floor muscles [3,11,12]. Therefore, the damage of nerves of the female genitourinary tract was an important reason for POP and SUI in females.…”
Section: Discussionmentioning
confidence: 99%